2020
DOI: 10.1177/1120672120977354
|View full text |Cite
|
Sign up to set email alerts
|

Vision-related quality of life in patients with a history of congenital glaucoma

Abstract: Purpose: To assess the vision-related quality of life in adult patients with a history of primary congenital glaucoma. Methods: In a cross-sectional hospital-based study eligible patients with a history of primary congenital glaucoma aged more than 18 were recruited in the study. Patients with secondary glaucoma and monocular patients were excluded. All patients underwent a complete ophthalmologic examination. The subjects were requested to answer a Persian approved version of the 25-item National Eye Institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
(38 reference statements)
0
9
0
2
Order By: Relevance
“…The majority of studies reported possible differences in patient’s QoL and FV in relation to their VA. The results across the studies measuring VR-QoL were mostly consistent, with seven papers reporting worse QoL in cases of increasing visual field deviation [ 79 , 81 ], worse VA [ 36 , 38 , 77 79 , 82 ], or worse postoperative VA [ 75 ]. Though, one study found the association with VA not to be important [ 81 ].…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The majority of studies reported possible differences in patient’s QoL and FV in relation to their VA. The results across the studies measuring VR-QoL were mostly consistent, with seven papers reporting worse QoL in cases of increasing visual field deviation [ 79 , 81 ], worse VA [ 36 , 38 , 77 79 , 82 ], or worse postoperative VA [ 75 ]. Though, one study found the association with VA not to be important [ 81 ].…”
Section: Resultsmentioning
confidence: 67%
“…Many of the included papers investigated associations between the main outcomes (i.e., QoL or FV) and at least one clinical, treatment, or disease-specific factor. For instance, the studies most frequently compared PF or QoL findings to glaucoma type or laterality [ 36 38 , 75 , 77 , 78 , 83 , 85 , 88 , 90 ], visual acuity (VA) [ 36 38 , 75 , 77 79 , 82 , 83 , 88 , 90 ], age at or duration since diagnosis [ 36 , 38 , 77 , 79 , 83 , 86 , 87 ], medication or treatment practices [ 36 , 71 , 75 , 77 79 , 81 – 83 , 88 ], and number and outcomes of glaucoma surgeries [ 36 , 38 , 75 , 77 79 , 81 – 83 , 85 – 88 ]. In relation to family and broader sociodemographic characteristics, researchers most frequently compared outcome measures to age, gender, marital status, parental education level, employment status, household income, socioeconomic status, and presence of another child with glaucoma in the family [ 36 38 , 75 , 77 79 , 81 , 83 , 85 – 88 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we should take caution in explaining the significant signal, as one of the complications of advanced neovascular AMD. Glaucoma is currently the leading cause of irreversible blindness worldwide (Quigley, 2006;Miraftabi et al, 2020) due to elevated intraocular pressure (Blumberg et al, 2015). Clinical ophthalmologists are also concerned about the increase of intraocular pressure after the administration of anti-VEGF drugs.…”
Section: Figurementioning
confidence: 99%
“…Современный этап развития офтальмологии характеризуется существенным повышением уровня практической значимости оценки «качества жизни» (КЖ) пациента, что связано с надежностью и достоверностью получаемых данных, а также наличием значимых корреляционных связей между КЖ и объективными клиническими показателями зрительной системы. К настоящему моменту опросники КЖ (общие или специальные) нашли достаточно широкое применение практически для всех актуальных видов глазной патологии [6][7][8][9][10][11][12].…”
Section: Introductionunclassified